Development of an automotive 42 V flywheel centrifugal permanent magnet generator and research on regulator control technology. (19th February 2014) - Zhang, Xueyi; Yin, Hongbin; Du, Qinjun; Shi, Liwei
Permanent magnet N and S poles of centrifugal flywheel permanent magnet generator are alternately fixed on the inner wall of the flywheel rotor, which makes the magnetic field directly face the air gap and reduces the magnetic flux leakage. Winding short moment coefficient, optimum value of stator outer diameter, permanent magnet size and winding turns are calculated. Parameters of the air–gap flux density, armature reaction magnetic field, the armature winding inductance and no–load induced electromotive force are obtained by simulation analysis by using the analytical method to obtain the optimal design parameters. A pulse width modulation regulator that is integrated into the power supply circuit, the reference circuit, the detection circuit, the oscillation circuit and the trigger circuit is developed, which makes the generator output voltage steady within a certain range. It solves the problem that the automotive flywheel centrifugal permanent magnet generator output voltage is unstable in a wide speed and load.